The Level of Community Participation in Land Registration Activities in Indonesia - Kusmiarto Kusmiarto; Heri Sutanta; Trias Aditya (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2020)
Abstract: Community participation in the implementation of government projects, including land registration activities, has now increasingly incorporated and mainstreamed. The public is encouraged and invited to actively participate in the various stages of land registration process. However, the extent of community participation in land registration activities in Indonesia has not been thoroughly investigated. This paper aims to examine the level of community participation in supporting the Complete Systematic Land Registration, known as PTSL in Indonesia. Classical and new theories on community participation were used as the framework. They include A Ladder of Citizen Participation, the Wheel of Participations, and Consultations Complexity Chart. All stages in the PTSL were identified and classified based on their levels or quadrants on the three theoretical models. The findings show that 13 out of 32 steps in the PTSL have public participation involvement, 7 steps potentially involve community participation and 12 of them have no community elements. Stages in PTSL that have community participation are located at a higher level of the ladder and the wheels, as well as the most complex part in the chart.Intisari: Partisipasi masyarakat dalam pelaksanaan kegiatan proyek-proyek pemerintah, termasuk pada kegiatan pendaftaran tanah, kini semakin diarusutamakan. Masyarakat didorong untuk terlibat dalam berbagai tahapan proses pendaftaran tanah secara aktif. Namun, sejauh mana partisipasi masyarakat dalam kegiatan pendaftaran tanah di Indonesia belum diteliti secara menyeluruh. Tulisan ini bertujuan untuk menilai tingkat partisipasi masyarakat dalam kegiatan Pendaftaran Tanah, yang dikenal sebagai PTSL di Indonesia. Teori klasik dan baru tentang partisipasi masyarakat digunakan sebagai kerangka kerja kajian ini. Teori-teori tersebut adalah Tangga Partisipasi, Roda Partisipasi, dan Bagan Kompleksitas Konsultasi. Semua tahapan dalam PTSL diidentifikasi dan diklasifikasikan berdasarkan level atau tingkatan, dan kuadran pada tiga model teoritis tersebut. Temuan menunjukkan bahwa 13 (tiga belas) dari 32 (tigapuluh dua) tahapan kegiatan dalam PTSL ada keterlibatan partisipasi masyarakat, 7 (tujuh) langkah berpotensi melibatkan partisipasi masyarakat dan 12 (dua belas) di antaranya tidak ada keterlibatan unsur masyarakat. Tahapan dalam PTSL dengan partisipasi masyarakat semakin menuju pada tangga partisipasi yang lebih tinggi, dan kuadran roda partisipasi yang lebih jauh, serta pada bagian paling kompleks dalam Bagan Kompleksitas Konsultasi.